2005
DOI: 10.1017/s1355617705050411
|View full text |Cite
|
Sign up to set email alerts
|

The neuropsychological impact of sports-related concussion: A meta-analysis

Abstract: There is increasing interest in the potential neuropsychological impact of sports-related concussion. A meta-analysis of the relevant literature was conducted to determine the impact of sports-related concussion across six cognitive domains. The analysis was based on 21 studies involving 790 cases of concussion and 2014 control cases. The overall effect of concussion (d 5 0.49) was comparable to the effect found in the non-sports-related mild traumatic brain injury population (d 5 0.54; Belanger et al., 2005).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
265
3
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(290 citation statements)
references
References 70 publications
21
265
3
1
Order By: Relevance
“…The literature is inconsistent regarding these effects 6 ; although a 2005 meta-analysis suggested that athletes typically demonstrate a full neuropsychological recovery in 7-10 days after concussion, 7 two recent studies demonstrated significant episodic memory impairments in middle-aged and older adults with a history of sport-related concussion. 8,9 In a recent review, Broglio and colleagues 6 suggested that such impairments are indicative of accelerated age-related cognitive decline from concussive and subconcussive head trauma.…”
Section: Introductionmentioning
confidence: 99%
“…The literature is inconsistent regarding these effects 6 ; although a 2005 meta-analysis suggested that athletes typically demonstrate a full neuropsychological recovery in 7-10 days after concussion, 7 two recent studies demonstrated significant episodic memory impairments in middle-aged and older adults with a history of sport-related concussion. 8,9 In a recent review, Broglio and colleagues 6 suggested that such impairments are indicative of accelerated age-related cognitive decline from concussive and subconcussive head trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms typically resolve within days or weeks and significant improvement is often seen in 3 months [14][15]. The most visible injuries (e.g., penetrating wounds) understandably receive the most attention in theater, but other symptoms may emerge or be reported later [16], after even a mild injury [17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Belanger and Vanderploeg's meta-analysis of the initial impact of sports-related concussion on neuropsychological test scores found an overall effect size equivalent to one-half of one standard deviation [13]. The largest specific effects involved global cognitive functioning, memory acquisition, and delayed memory, and cognition typically returned to normal within 1 week [13][14].…”
Section: Definition Of Concussionmentioning
confidence: 99%
“…The largest specific effects involved global cognitive functioning, memory acquisition, and delayed memory, and cognition typically returned to normal within 1 week [13][14]. In a meta-analysis of MTBI from causes other than sports injuries, Belanger et al found an overall cognitive effect size similar to that found in sports, with the largest specific effects for delayed memory and fluency [15].…”
Section: Definition Of Concussionmentioning
confidence: 99%